Studi Komparasi Kepuasan Pasien BPJS Dan Non BPJS Pada Mutu Pelayanan Pendaftaran Puskesmas Johar Baru Jakarta Pusat - Maya Sofiana; Rita Wahyuni; Endang Supriyadi (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
The patient registration service is the starting gate for the health center services. In implementing BPJS, the community expects to get satisfactory health services.  Patients will feel or not depends on the quality of registration services provided. If the patient feels satisfied the he will come back to get health care. However, if the patient is not satisfied, there will be many complaints that will not only be delivered face-to-face but more than that it can occur the complaint is submitted thorugh print media, visual media, and even social media.  The purpose of study was to determine the comparative satisfaction of BPJS and non BPJS patients on the quality of registration services at the Johar Baru Health Center in Central Jakarta.riptive method with a Cross Sectional Comparative approach in the registration section at Johar Baru Health Center, Central Jakarta Research methods. This research was conducted with a descriptive method with a Cross Sectional Comparative approach in the registration section at Johar Baru Health Center, Central Jakarta.  The population in this study were BPJS and Non BPJS patients who registered at the outpatient Registration in October-December 2019.  The method of selecting samples was used with probability sampling whie to take samples using the proportionate stratified random sampling technique.  The tool used for research with Questionnaire/Questionnaire. With a Likert scale measurement scale.  For data analysis techniques using the Vality Test used is the product moment correlation which results in that the whoe question items are valid, which decision considerations are based on the r table for N = 30 at a significance of 5%, amounting to 0.361.Realibility Tests are used to show the extent to which a measurement result is relatively consistent if our measuring instrument repeatedly.  Based on the reliability test, for the item questionnaire, the decision consideration is based on Cronbach’salfa value>0.60, the questionnaire is declared reliable or consistent. In this study the Cronvachs’s Alfa Value of 0.699 ‘s was rounded to 0.70, the cronbanch Alfa Value of 0.70>0.60, the questionnaire was declared reliable or consistent. With cross sectional time approach. The Mann Whitney U test was used to prove the hypothesis with the SPSS For Windows 25 software version, the significance value or Symp was obtained. Sig, (2 tailed) of 0.001. Therefore the value of Symp. Sig, (2 tailed) of 0.001>from the probability of 0.0f, the hypothesis “Ha is a accepted” or there is a difference. Based on the average value in the level of BPJS patient satisfaction obtained an average of 79.96 for Non BPJS patients obtained an average of 76.13 while the difference between the two amounted to 3.83. Targeted Output.  Is a scientific publication in the National Journal of ISSN submitted, speakers in scientific meetings are registered, teaching material (ISBN) draft newspapaer articles are published. The proposed TKT research is TKT 1    The patient registration service is the starting gate for the health center services. In implementing BPJS, the community expects to get satisfactory health services.  Patients will feel or not depends on the quality of registration services provided. If the patient feels satisfied the he will come back to get health care. However, if the patient is not satisfied, there will be many complaints that will not only be delivered face-to-face but more than that it can occur the complaint is submitted thorugh print media, visual media, and even social media.  The purpose of study was to determine the comparative satisfaction of BPJS and non BPJS patients on the quality of registration services at the Johar Baru Health Center in Central Jakarta.riptive method with a Cross Sectional Comparative approach in the registration section at Johar Baru Health Center, Central JakartaResearch methods. This research was conducted with a descriptive method with a Cross Sectional Comparative approach in the registration section at Johar Baru Health Center, Central Jakarta.  The population in this study were BPJS and Non BPJS patients who registered at the outpatient Registration in October-December 2019.  The method of selecting samples was used with probability sampling whie to take samples using the proportionate stratified random sampling technique.  The tool used for research with Questionnaire/Questionnaire. With a Likert scale measurement scale.  For data analysis techniques using the Vality Test used is the product moment correlation which results in that the whoe question items are valid, which decision considerations are based on the r table for N = 30 at a significance of 5%, amounting to 0.361.Realibility Tests are used to show the extent to which a measurement result is relatively consistent if our measuring instrument repeatedly.  Based on the reliability test, for the item questionnaire, the decision consideration is based on Cronbach’salfa value>0.60, the questionnaire is declared reliable or consistent. In this study the Cronvachs’s Alfa Value of 0.699 ‘s was rounded to 0.70, the cronbanch Alfa Value of 0.70>0.60, the questionnaire was declared reliable or consistent. With cross sectional time approach. The Mann Whitney U test was used to prove the hypothesis with the SPSS For Windows 25 software version, the significance value or Symp was obtained. Sig, (2 tailed) of 0.001. Therefore the value of Symp. Sig, (2 tailed) of 0.001>from the probability of 0.0f, the hypothesis “Ha is a accepted” or there is a difference. Based on the average value in the level of BPJS patient satisfaction obtained an average of 79.96 for Non BPJS patients obtained an average of 76.13 while the difference between the two amounted to 3.83.Targeted Output.  Is a scientific publication in the National Journal of ISSN submitted, speakers in scientific meetings are registered, teaching material (ISBN) draft newspapaer articles are published. The proposed TKT research is TKT 1